Two regimes of ionization-induced recovery in SrTiO3 under irradiation. (December 2019) - Weber, William J.; Xue, Haizhou; Zarkadoula, Eva; Zhang, Yanwen
Abstract: Irradiation of pre-damaged SrTiO3 with 2 MeV He, 1.2 MeV C, 5 MeV C and 12 MeV O ions reveals two regimes of ionization-induced recovery. For C and O ions, with electronic energy loss between 1.6 and 3 keV/nm, recovery cross-sections range from 0.27 to 0.38 nm 2, and molecular dynamics confirms recovery related to ionization-induced thermal spikes via electron-phonon coupling. At lower electronic energy losses, recovery cross-sections decrease to about 5.5 × 10 −4 nm 2 for 2 MeV He ions and 1.0 × 10 −5 nm 2 for 200 keV electrons, which suggests recovery associated with local electronic excitation processes. Graphical abstract: Unlabelled Image